AWARENESS AND SKILL AS DETERMINANT FACTORS IN THE APPLICATION OF STRATEGIC COST MANAGEMENT IN SOUTH AFRICAN STATE-OWNED ENTITIES - Mchavi, Nyiko D.; Ngwakwe, Collins, C (Jurnal Bisnis dan Keuangan, 2025)
This study investigates how awareness and skill influences the adoption of Strategic Cost Management (SCM) in South African State-Owned Enterprises (SOEs). Therefore, it explores the roles of awareness and skill in SCM application, and examines their impact on the decision to implement SCM. The paper applied a quantitative technique, and data was collected by using a survey questionnaire, which was distributed to officials of state owned entities. Data was analysed to determine if SOEs apply Strategic Cost Management (particularly TC and ABM), and if awareness and skill in usage of SCM affect commitment to apply it. The data was analysed by applying the ordinal regression model. Key findings reveal that while there is a general awareness of SCM among SOE employees, the level of skills and knowledge varies significantly. Moreover, the study demonstrates a strong correlation between awareness and skill in SCM and the decision to implement it. This, in turn, can lead to improved financial performance, increased efficiency, and greater accountability. The study provides valuable insights for policymakers and SOE management on strategies to enhance the adoption and impact of SCM in South Africa.